Structure and Luminescence Properties of InGaN/AlGaN Multiquantum‐Well Microrod Array Structures. Issue 6 (19th January 2022) - Du, Jinjuan; Xu, Shengrui; Peng, Ruoshi; Zhao, Ying; Fan, Xiaomeng; Tao, Hongchang; Zhang, Jincheng; Hao, Yue
Abstract : The InGaN/AlGaN multiquantum‐well microrod‐array structure is grown on c‐plane GaN template with SiO2 microholes patterned as a mask. The surface morphology exhibits the accurately ordered microrod‐array structure. Temperature‐dependent photoluminescence (PL) measurement indicates that the PL peaks redshift as the temperature increases. Room‐temperature PL and cathode luminescence spectra show that the different positions on InGaN/AlGaN microrod arrays have different luminous peaks. The successful fabrication of InGaN/AlGaN microrod arrays is of great significance for the realization of multicolor emission and the design of new optoelectronic devices. Abstract : The InGaN/AlGaN multiquantum‐well microrod array structure grown on c‐plane GaN template exhibits accurately ordered microrod array structures. Room‐temperature photoluminescence and cathode luminescence spectra show that the different positions on InGaN/AlGaN microrod arrays have different luminous peaks. The successful fabrication of InGaN/AlGaN microrod arrays is of great significance for the realization of multicolor emission and the design of new optoelectronic devices.